THE EFFECTIVENESS OF ANIMATED VIDEOS IN ENHANCING READING COMPREHENSION AMONG THE SEVENTH-GRADE STUDENTS - Tri Idayanti; Elok Widiyati (JEELL (Journal of English Education, Linguistics and Literature), 2025)
Reading comprehension involves understanding and interpreting text, which can be particularly difficult for learners of a foreign language. This study aimed to assess how effective animated videos are in enhancing the reading comprehension of seventh grade students. This study employed an experimental approach using a quasi-experimental design. The participants were from the VII A and VII B at a Private Junior High School in Jepara, consisting of 46 students. It involved two groups: an experimental group used animated videos to teach reading comprehension, and a control group did not use them. Both groups received a pre-test and post-test to measure reading comprehension of descriptive text, which consisted of 20 multiple- choice questions validated by two experts. The collected data were analyzed using SPSS 25.0. The resulting data analysis indicated a significant difference between both groups, where the experimental group achieved an average test score of 77.73, which was higher than control group with a score of 69.17. The statistical test showed a significant score (2-tailed) of 0.026 (p < 0.05). These results highlight the potential of animated videos as an effective instructional medium for enhancing students’ reading comprehension of descriptive texts.